When sensing is gambling: An experimental system reveals how plasticity can generate tunable bet‐hedging strategies. (7th March 2017) - Maxwell, Colin S.; Magwene, Paul M.
Abstract : Genotypes can persist in unpredictable environments by "hedging their bets" and producing diverse phenotypes. Theoretical studies have shown that the phenotypic variability needed for a bet‐hedging strategy can be generated by factors either inside or outside an organism. However, sensing the environment and bet hedging are frequently treated as distinct evolutionary strategies. Furthermore, nearly all empirical studies of the molecular underpinnings of bet‐hedging strategies to date have focused on internal sources of variability. We took a synthetic approach and constructed an experimental system where a phenotypic trade‐off is mediated by actively sensing a cue present in the environment. We show that active sensing can generate a diversified bet‐hedging strategy. Mutations affecting the norm of reaction to the cue alter the diversification strategy, indicating that bet hedging by active sensing is evolvable. Our results indicate that a broader class of biological systems should be considered as potential examples of bet‐hedging strategies, and that research into the structure of environmental variability is needed to distinguish bet‐hedging strategies from adaptive plasticity.